165k views
4 votes
A^2(64a^2-3)/3=27-4a^2/4

A^2(64a^2-3)/3=27-4a^2/4-example-1
User Swimmer
by
5.3k points

1 Answer

2 votes
The answer is a = 3/4 = 0.75

First get rid of the paranthesis,

{a}^(2) (64 {a}^(2) - 3) = 64 {a}^(4) - 3 {a}^(2)
Then set the denominators equal:

\frac{ 256 {a}^(4) - 12 {a}^(2)}{12} = \frac{81 - 12 {a}^(2) }{12}
Then remove the denominators and solve:

256 {a}^(4) - 12 {a}^(2) = 81 - 12 {a}^(2)
Eliminate -12a^2 by adding 12a^2 to both sides:

256 {a}^(4) = 81
Take the fourth root of them or take the square root twice:

\sqrt[4]{256 {a}^(4) } = \sqrt[4]{81} \\ 4a = 3
Divide both sides by 4:

a = (3)/(4) = 0.75
User Paul Russell
by
5.1k points